The Politics of the Senate Reform Reference: Fidelity, Frustration, and Federal Unilateralism - Dodek, Adam (McGill Law Journal / Revue de droit de McGill, 2015)
References are the most political of cases, almost always involving high profile public policy issues. Frequently, references are brought to obtain rulings on the relationship between the federal government and the provinces. Less frequently, references involve questions of interbranch relations, that is, between two or more of the executive, legislative, and judicial branches of government. The Senate Reform Reference was one of the rare cases that featured each of these three elements. This article analyzes the Senate Reform Reference on several political levels. First, it situates the reference in terms of megaconstitutional politics, the long-held Canadian practice of attempting to resolve constitutional issues through formal and often high-profile negotiations between the federal and provincial governments. Such interactions have been anathema to the Harper government which has preferred unilateral political action to negotiated political agreement. The article then examines interparty politics or the relationship between the Harper government and the opposition parties during the period of minority government (2006–2011). This is the period during which one would have expected the government to bring a reference because of its inability to obtain support from the other parties in the House of Commons and the Senate for its proposed legislation on the Senate. However, it did not. This leads to an examination of the third issue: intra-party politics or the politics within the governing party, the Conservative Party of Canada. Finally, the article discusses legal politics and how the government of Québec essentially forced the federal government’s hand by bringing its own reference to the Québec Court of Appeal. The overarching framework of interbranch politics—the relationship between the executive, legislative and judicial branches of government—is examined throughout the article.